Czy wiedźmin może nauczyć grzeczności? Elementy etykiety językowej w "Ostatnim życzeniu" Andrzeja Sapkowskiego = Can a witcher teach politeness? Elements of a linguistic etiquette in Andrzej Sapkowski`s "Last Wish" - Choruży, Igor; Gorzelana, Joanna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article presents how the heroes of A. Sapkowski`s stories implement the principles of savoir-faire. The text describes the forms of address that reflect the system of social hierarchy and the characters? emotions. It also outlines other first-rate courtesies such as greetings, farewells, pleas, thanks and apologies.
Keywords: grzeczność; akt grzecznościowy; wiedźmin; Sapkowski, Andrzej (1948- ); courtesy; the act of courtesy; witcher